MODEL TGT BERBANTUAN MEDIA EDUCAPLAY DALAM MENINGKATKAN PEMBELAJARAN DI SEKOLAH DASAR - Nova Suci Pertiwi; Abdul Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Educaplay game-based Team Games Tournament (TGT) model is one of the media or approaches that integrate learning materials using technology. The purpose of this study was to determine whether the Team Games Tournament cooperative learning model (TGT) assisted by Educaplay can improve students' cooperative attitudes and activeness in the classroom during the learning process. This study is a literature review study with a descriptive review type. The scientific articles used in this study amounted to 30 scientific articles originating from 2 international articles, 15 articles accredited in national journals, and 13 articles proceedings in the Google Scholar database with a publication range of 2022-2026. The data presentation technique uses a table that lists the scientific publication articles that will be analyzed as research data. The data analysis technique was carried out descriptively by analyzing and identifying scientific articles to produce a more informative summary. The results of research based on articles that have been conducted show that the Educaplay-based Team Games Tournament learning model can significantly improve learning outcomes in understanding the concepts of learning Mathematics, Indonesian, Social Sciences, Natural Sciences, Pancasila Education, Physical Education, and English. By using the Educaplay platform, students can improve their critical thinking skills with the ability to work together in fostering a sense of responsibility in solving problems and understanding learning materials in depth.